Addition of propolis or monensin in the diet: Behavior and productivity of lambs in feedlot - Itavo, C. C. B. F.; Morais, M.G.; Costa, C. [UNESP]; Itavo, L. C. V.; Franco, G. L.; da Silva, J. A.; Reis, F. A. (Elsevier B.V., 2011)
This study assessed the behavior and the productive performance of lambs finished in feedlot receiving diets added with green propolis, brown propolis or monensin sodium. The experiment used a randomized block design that compared weight gain of 32 male lambs aged four months among four dietary treatments: (1) control, non-enriched diet; (2) with green propolis; (3) with brown propolis; and (4) with monensin sodium. The basic diet provided to all the groups was a total mixed ration (TMR) with a forage:concentrate ratio of 50:50, in which Tifton 85 (Cynodon spp.) grass was used as roughage feed and the concentrate was based on soybean meal, corn meal and minerals. The green propolis diet decreased rumination and increased resting time. The diets provided similar feeding rate (g/min). DM and aNDF intake (g/kg of body weight and g/kg of metabolic weight) were higher in the control treatment. Although the control group had the highest weight gain, the highest feed conversion and feed efficiency were found in lambs fed brown propolis and monensin sodium. Technically, brown propolis can substitute monensin sodium as a dietary additive for feedlot lambs. However, complementary studies are needed to identify the best levels of brown propolis to add to these diets. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Feedlot; Feed conversion; Feed efficiency; Ethogram; Sheep; Rumination